Dealing With Stress in Cats: What Is New About the Olfactory Strategy? - Zhang, Lingna; Bian, Zhaowei; Liu, Qingshen; Deng, Baichuan (Frontiers in Veterinary Science, 2022)
Domestic cats are descended from solitary wild species and rely heavily on the olfaction system and chemical signals for daily activities. Cats kept as companion animals may experience stress due to a lack of predictability in their physical or social environment. The olfactory system is intimately connected to the brain regions controlling stress response, thus providing unique opportunities for olfactory strategies to modify stress and related behavioral problems in cats. However, olfactory intervention of stress in cats has been mainly focused on several analogue chemical signals and studies often provide inconsistent and nonreplicable results. Supportive evidence in the literature for the potentially effective olfactory stimuli (e.g., cheek and mammary gland secretions, and plant attractants) in treating stress in cats were reviewed. Limitations with some of the work and critical considerations from studies with natural or negative results were discussed as well. Current findings sometimes constitute weak evidence of a reproducible effect of cat odor therapy for stress. The welfare application of an olfactory stimulus in stress alleviation requires a better understanding of its biological function in cats and the mechanisms at play, which may be achieved in future studies through methodological improvement (e.g., experiment pre-registration, appropriate control setting) and in-depth investigation with modern techniques that integrate multi-source data. Contributions from individual and environmental differences should be considered for the stress response of a single cat and its sensitivity to olfactory manipulation. Olfactory strategies customized for specific contexts and individual cats can be more effective in improving welfare of cats in various stressful conditions.